Peningkatan performan entog dengan pemberian ransum komplit berbasis batang pisang - Dini Widianingrum; Iwan Setiawan; Oki Imanudin; Rachmat Somanjaya (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Muscovy duck was in demand by breeders because of easy maintenance, fast growth, and quick yielding. But muscovy ducks have a high level of ration consumption, resulting in high production costs. An alternative solution used cheap, abundant, and good feed nutrient ingredients, including banana stems. The objective of the research was to obtain the best performance of muscovy duck served a complete ration based on banana stems. The method used was an experimental method with a completely randomized design to 100 ducks with 5 treatments and 4 replication P0 (ration without (0%) banana stems), P1 (ration containing 25% banana stems), P2 (ration containing 50% banana stems), P3 (ration containing banana stems 75%), and P4 (85% banana stems). Maintenance of muscovy duck started from 4 to 12 weeks of age. The variables observed were ration consumption, body weight, and ration conversion. The results showed that the muscovy duck which was served a complete ration containing 50% stems showed the best musk performance, including ration consumption of 31,42+0,00 kg, daily ration consumption 52,37+0,00 gram/day, bodyweight of 24,27+0,00 kg, body weight gain 40,46+0,01 gram/day and ration conversion of 1.29+0,00. In conclusion, the best complete muscovy duck ration contains 50% banana stems.